Pendugaan Korelasi antara Karakteristik Tanah terhadap Cadangan Karbon pada Tegakan Shorea javanica K. et. V. di BKPH Jasinga Leuwiliang - Omo Rusdiana; Erwin Sianturi (Jurnal Silvikultur Tropika, 2020)
Forest as a natural resource that plays an important role in the lives of living beings either directly or indirectly. This research aims to calculate and determine the correlation of the characteristics of the soil carbon storage in the soil surface on Shorea javanica that planted in 2004 and 2007 at BKPH Jasinga Leuwiliang. The potential of carbon that storage in the soil surface in BKPH Jasinga Leuwiliang are varieted in 6 research plots with the carbon that is at most 3 plots of 3601.10 kg/ha or approximately 35.54% of the total carbon in the area and most are low in 5 plots of 499.07 kg/ha or about 4.9% of the total carbon in all the plots. Chemical analysis showed that the land average value is pH = 4.19, organic C = 3.18%, BO = 5.53%, N-total = 0.38%, C/N = 8.55%, P = 13.96 ppm, Kdd = 0.21 me/100g, CEC = 0.21 me/100g, BD = 0.77 g/cm3, and the porosity = 0.71%. The value of soil characteristics on research plots, both physically and chemically are classified as low to moderate where the correlation between the characteristics of the soil in the research field did not have a significant relation to the carbon stored. Keywords: BKPH Jasinga, carbon, correlation, Shorea javanica, soil characteristics